2015
DOI: 10.1021/acs.jpcb.5b07494
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Memory of a Protein Revealed by Single-Molecule Spectroscopy

Abstract: Proteins are supramolecular machines that carry out a wide range of different functions, many of which require flexibility. Up until now spontaneous conformational fluctuations of proteins have always been assumed to reflect a stochastic random process. However, if changing between different conformational states was random, then it would be difficult to understand how conformational control of protein function could have evolved. Here we demonstrate that a single protein can show conformational memory. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 43 publications
4
19
0
Order By: Relevance
“…PLN regulates SERCA by altering the transition between the E2 and E1 conformational states, which manifests as a decrease in SERCA's calcium affinity. Herein, our data are consistent with conformational memory (36) in the SERCA-PLN regulatory complex. The SERCA-PLN complex attains distinct structural states depending on substrate conditions (Fig.…”
Section: Conformational Memory In the Serca-pln Regulatory Complexsupporting
confidence: 88%
See 1 more Smart Citation
“…PLN regulates SERCA by altering the transition between the E2 and E1 conformational states, which manifests as a decrease in SERCA's calcium affinity. Herein, our data are consistent with conformational memory (36) in the SERCA-PLN regulatory complex. The SERCA-PLN complex attains distinct structural states depending on substrate conditions (Fig.…”
Section: Conformational Memory In the Serca-pln Regulatory Complexsupporting
confidence: 88%
“…Moreover, once a particular SERCA-PLN inhibitory interaction was established, it persisted during continuous catalytic turnover of SERCA. This "conformational memory" (36) in the SERCA-PLN regulatory complex provides insights into the functional relevance of the published crystal structures of SERCA bound to PLN (11) and SLN (9,10).…”
mentioning
confidence: 91%
“…The authors in the latter study further argue that conformational memory, in contrast to purely stochastic conformational switching, is a precondition for functional control of native light-harvesting [41].…”
Section: Characterization Of Isolated Complexesmentioning
confidence: 92%
“…In a later study of the LH2 complexes in a polymer film it was found that the same pigment-protein supramolecule can have different number (namely, 80 two, three or four) of conformational states [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…For the LH2 complex of Rps.acidophila, considering its C 9 symmetry, the number of structurally different and symmetrically non-equivalent metastable conformations is 59[77], including 1 singly ligated and 4 doubly ligated. The actual number of such conformations is unknown, and the number assumed theoretically to account for experimental data on spectroscopic shifts and fluorescence intermittency greatly varies: two to four per each BCL in B850 ring[14], two per BCL[42,43], two or three per complex [15] and up to four per complex[44].Two motions are needed for the formaton of metastable conformational state of the LH2 complex: an acetyl group rotation associated with a hydrogen bond break and a shift of a BCL molecule towards a neighboring one. According to our MD results, these two motions occur at significantly different rates, BCL…”
mentioning
confidence: 99%